2017
DOI: 10.1242/jeb.152918
|View full text |Cite
|
Sign up to set email alerts
|

Optical influence of oil droplets on cone photoreceptor sensitivity

Abstract: Oil droplets are spherical organelles found in the cone photoreceptors of vertebrates. They are generally assumed to focus incident light into the outer segment, and thereby improve light catch because of the droplets' spherical lens-like shape. However, using full-wave optical simulations of physiologically realistic cone photoreceptors from birds, frogs and turtles, we find that pigmented oil droplets actually drastically reduce the transmission of light into the outer segment integrated across the full visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In support of this, human dichromats with red-green color blindness do not appear to develop significantly more refractive error than trichromats – indeed, some forms of red/green color blindness may actually be protective against myopia (Qian, Chu et al 2009) suggesting that the red/green system can sometimes interfere with emmetropization. On the other hand, chicks come from a long evolutionary lineage of tetrachromacy, and use oil droplets to further sharpen the wavelength tuning of their cones (Wilby and Roberts 2017). We should not therefore be surprised if the emmetropization systems of mammals and birds both use wavelength cues, but differ in how they use them.…”
Section: 0 Discussionmentioning
confidence: 99%
“…In support of this, human dichromats with red-green color blindness do not appear to develop significantly more refractive error than trichromats – indeed, some forms of red/green color blindness may actually be protective against myopia (Qian, Chu et al 2009) suggesting that the red/green system can sometimes interfere with emmetropization. On the other hand, chicks come from a long evolutionary lineage of tetrachromacy, and use oil droplets to further sharpen the wavelength tuning of their cones (Wilby and Roberts 2017). We should not therefore be surprised if the emmetropization systems of mammals and birds both use wavelength cues, but differ in how they use them.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The occurrence of colorless (and presumably carotenoid-free) oil droplets in multiple vertebrate clades implies a function aside from spectral filtering. Indeed, even without pigmentation, cone oil droplets are highly refractile (Young and Martin, 1984 ; Wilby et al, 2015 ; Wilby and Roberts, 2017 ). Multiple modeling studies have suggested that oil droplets collect light and focus it into the outer segment, enhancing light capture and thereby increasing cone sensitivity (Baylor and Fettiplace, 1975 ; Govardovskii et al, 1981 ; Ives et al, 1983 ; Young and Martin, 1984 ; Stavenga and Wilts, 2014 ).…”
Section: The Light-collecting Function Of Oil Dropletsmentioning
confidence: 99%
“…The droplets consist of colorless neutral lipids pigmented with a range of carotenoids that endow the droplets of different cone subtypes with colors ranging from transparent to brilliant red (Goldsmith et al, 1984 ). Recent studies indicate that oil droplets have two main functions: they act as intracellular microlenses that enhance light delivery to the outer segment (Stavenga and Wilts, 2014 ; Wilby et al, 2015 ; Wilby and Roberts, 2017 ); and they filter the spectrum of light reaching the outer segment, thereby improving color discrimination and color constancy (Vorobyev et al, 1998 ; Vorobyev, 2003 ; Olsson et al, 2016 ). Enhancement of light delivery is primarily observed in colorless droplets, since light-filtering by carotenoids reduces the amount of light reaching the outer segment, thereby negating the lensing effect.…”
Section: Introductionmentioning
confidence: 99%
“…The identity of the light pink peripheral cells surrounding the central granular ones is also uncertain. The presence of an oil droplet in each of them may be a clue suggesting that they are photosensitive, as oil‐droplets are a fairly common feature in the cones of vertebrates where they apparently act as microlenses which focus incident light into the outer segment (Stavenga & Wilts, ; Wilby & Roberts, ). For greater clarity of the identity and function of the central and peripheral cells in the eye of T. vermis, further investigation is obviously needed, including the use of electron microscopy to study them at ultra‐structural level.…”
Section: Discussionmentioning
confidence: 99%